Auction market placement and a rest stop during transportation affect the respiratory bacterial microbiota of beef cattle - Uddin, Muhammed Salah; Schwartzkopf-Genswein, Karen S.; Waldner, Matthew; Meléndez, Daniela M.; Niu, Yan D.; Alexander, Trevor W. (Frontiers in Microbiology, 2023)
Background: Bovine respiratory disease (BRD) is a significant health problem in beef cattle production, resulting in considerable economic losses due to mortalities, cost of treatment, and reduced feed efficiency. The onset of BRD is multifactorial, with numerous stressors being implicated, including transportation from farms to feedlots. In relation to animal welfare, regulations or practices may require mandatory rest times during transportation. Despite this, there is limited information on how transportation and rest stops affect the respiratory microbiota.Results: This study evaluated the effect of cattle source (ranch-direct or auction market-derived) and rest stop duration (0 h or 8 h of rest) on the upper respiratory tract microbiota and its relationship to stress response indicators (blood cortisol and haptoglobin) of recently weaned cattle transported for 36 h. The community structure of bacteria was altered by feedlot placement. When cattle were off-loaded for a rest, several key bacterial genera associated with BRD (Mannheimia, Histophilus, Pasteurella) were increased for most sampling times after feedlot placement for the ranch-direct cattle group, compared to animals given no rest stop. Similarly, more sampling time points had elevated levels of BRD-associated genera when auction market cattle were compared to ranch-direct. When evaluated across time and treatments several genera including Mannheimia, Moraxella, Streptococcus and Corynebacterium were positively correlated with blood cortisol concentrations. Conclusions: This is the first study to assess the effect of rest during transportation and cattle source on the respiratory microbiota in weaned beef calves. The results suggest that rest stops and auction market placement may be risk factors for BRD, based solely on increased abundance of BRD-associated genera in the upper respiratory tract. However, it was not possible to link these microbiota to disease outcome, due to low incidence of BRD in the study populations.Larger scale studies are needed to further define how transportation variables impact cattle health.